From Fundamental Science to Product: A Bottom-up Approach to Sunscreen Development. (March 2018) - Rodrigues, Natércia d.N.; Stavros, Vasilios G.
Despite the pivotal role of ultraviolet (UV) radiation in sustaining life on Earth, overexposure to this type of radiation can have catastrophic effects, such as skin cancer. Sunscreens, the most common form of artificial protection against such harmful effects, absorb UV radiation before it reaches vulnerable skin cells. Absorption of UV radiation prompts ultrafast molecular events in sunscreen molecules which, ideally, would allow for fast and safe dissipation of the excess energy. However, our knowledge of these mechanisms remains limited. In this article, we will review recent advances in the field of ultrafast photodynamics (light induced molecular processes occurring within femtoseconds, fs, 10 −15 s to picoseconds, ps, 10 −12 s) of sunscreens. We follow a bottom-up approach to common sunscreen active ingredients, analysing any emerging trends from the current literature on the subject. Moreover, we will identify the main questions that remain unanswered, pinpoint some of the main challenges and finally comment on the outlook of this exciting field of research.